A Complication of Negative Resistance Circuits Generated by Two Novel Algorithms. (2002) - Kumar, Umesh
Abstract : There are two algorithms to generate a negative-resistance device which exhibits either a type-N shaped V-1 characteristic similar to a tunnel diode, or a type-S shaped V-1 characteristic similar to a four layered pnpn diode. We present here a selection of these circuits using bipolar, JFET or MOSFET or their combinations.